Influence of Air Pollution on Degradation of Historic Buildings at the Urban Tropical Atmosphere of San Francisco de Campeche City, México - Reyes, Javier; Corvo, Francisco; Espinosa-Morales, Yolanda; Dzul, Brisvey; Perez, Tezozomoc; Valdes, Cecilia; Aguilar, Daniel; Quintana, Patricia (IntechOpen, 2011)
None